1994
DOI: 10.1002/gepi.1370110104
|View full text |Cite
|
Sign up to set email alerts
|

Linkage between the APOB gene and serum apoB levels in a large pedigree from the Bogalusa heart study

Abstract: Maximum likelihood linkage analyses were performed to test for linkage between serum apoB levels and several candidate gene markers including apolipoprotein B, lipoprotein lipase, hepatic lipase, cholesterol ester transfer protein, and apolipoprotein AI in a large pedigree. Parameters of general Mendelian inheritance derived from maximum likelihood segregation analysis of the serum apoB levels were used in the linkage analysis. The highest two-point lod score between the quantitative trait and a marker defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…We previously identified evidence by segregation analysis, for a major gene effect on ApoB levels in this pedigree, with 42% of the variance attributed to a putative major locus. Using model-dependent methods of linkage analysis [Ott, 1991], we also found evidence of linkage between quantitative levels of serum ApoB and the APOB structural gene [Laing et al, 1994], but we did not find statistically significant evidence concerning ApoB levels using the Haseman-Elston method [Heiba et al, 1993]. For the current analysis, we first divided the extended family into nuclear families and then used either (1) the VC method assuming multivariate normality (scoring), or (2) the VC approach and QL.…”
Section: Data From the Bogalusa Heart Studymentioning
confidence: 84%
See 1 more Smart Citation
“…We previously identified evidence by segregation analysis, for a major gene effect on ApoB levels in this pedigree, with 42% of the variance attributed to a putative major locus. Using model-dependent methods of linkage analysis [Ott, 1991], we also found evidence of linkage between quantitative levels of serum ApoB and the APOB structural gene [Laing et al, 1994], but we did not find statistically significant evidence concerning ApoB levels using the Haseman-Elston method [Heiba et al, 1993]. For the current analysis, we first divided the extended family into nuclear families and then used either (1) the VC method assuming multivariate normality (scoring), or (2) the VC approach and QL.…”
Section: Data From the Bogalusa Heart Studymentioning
confidence: 84%
“…The HDL-C and ApoB levels were log-transformed before the analysis. Following the analyses reported here and in previous publications [Laing et al, 1994;Amos et al, 1987], effects of age, age squared, sex, oral contraceptive use, alcohol consumption, and smoking behavior were statistically removed by a regression analysis and obtaining the residuals. The residuals were subsequently standardized to have unit variance.…”
Section: Data From the Bogalusa Heart Studymentioning
confidence: 99%
“…Linkage between Apo-B levels and haplotypes at the Apo-B gene was even stronger. The XbaI site however, did not show evidence of linkage (Liang et al 1994).…”
Section: Discussionmentioning
confidence: 79%
“…Previous family studies have failed to reveal significant linkage between the Apo-B gene and either Apo-B levels (Coresh et al 1992b) or LDL subclass phenotypes (Austin et al 1991, La-Belle et al 199 1). Yet, maximum likelihood linkage analysis performed to test for linkage between Apo-B levels and several candidate gene markers including Apo-B in a large pedigree ascertained through an adolescent girl with a heart murmur and with a family history of CHD, revealed a significant linkage between Apo-B levels and the PvuII restriction site in the Apo-B gene (lod score=1.86 at recombination fraction (+)=O.O) (Liang et al 1994). Linkage between Apo-B levels and haplotypes at the Apo-B gene was even stronger.…”
Section: Discussionmentioning
confidence: 99%
“…The Bogalusa heart studies [30][31][32][33] have presented a considerable body of evidence on the genetic and epidemiological dynamics of lipids and apolipoprotein concentrations as they relate to the risk of CHD across races and genders, but have no endpoint data as yet. The few studies that have examined the association of hyperlipidaemia with CHD in minorities have shown that total cholesterol was a predictor of CHD risk.…”
Section: Agt235 Polymorphism and Cad Riskmentioning
confidence: 99%